Correlation between clinical and radiological grading of osteoarthritis - Singh, S.; Khanna, V. (Scientific Journal of Medical Science, 2014)
Primary knee Osteoarthritis is a common condition affecting human beings after fourth decade of life. The diagnosis is based on a) Clinical presentation alone or b) on clinical and radiological findings or c) on clinical presentation, radiological findings and laboratory results. Hence, correlation between clinical scoring and radiological staging is helpful in predicting the severity as well as clinical outcome of the disease. We screened 100 female patients suffering from primary knee pain for atleast 6 months of duration or more. All cases with secondary causes of knee osteoarthrits were excluded from the study. All cases were asked to get an anteroposterior standing radiograph of the involved knee and radiological assessment was done by Kellegren Lawrence grading (K-L grading) method. They were also asked to fill up the WOMAC questionnaire while waiting for the radiograph to develop. The results thus obtained were compared and correlated with the help of Pearson’s coefficient of correlation. The mean WOMAC score is found to be 51(max.81, min.17). The better the WOMAC score, the greater grade of severity according to KL grading was obtained. The Pearsons coefficient of correlation was calculated to be +0.904. The result shows a directly proportional relation between WOMAC score and K- L grading. Hence, with accurate history taking and clinical examination as well as WOMAC scoring one can predict the occurrence of knee Osteoarthritis earlier than its radiological appearance. Hence, giving more time to halt the progression of the disease at a much earlier stage when the destruction is at the cartilage level with no or very little bony destruction.